Systemic nanoparticle delivery of CRISPR-Cas9 ribonucleoproteins for effective tissue specific genome editing - Wei, Tuo (Nat Commun, 2020)
CRISPR-Cas9 has emerged as a powerful technology that relies on Cas9/sgRNA ribonucleoprotein complexes (RNPs) to target and edit DNA. However, many therapeutic targets cannot currently be accessed due to the lack of carriers that can deliver RNPs systemically. Here, we report a generalizable methodology that allows engineering of modified lipid nanoparticles to efficiently deliver RNPs into cells and edit tissues including muscle, brain, liver, and lungs. Intravenous injection facilitated tissue-specific, multiplexed editing of six genes in mouse lungs. High carrier potency was leveraged to create organ-specific cancer models in livers and lungs of mice though facile knockout of multiple genes. The developed carriers were also able to deliver RNPs to restore dystrophin expression in DMD mice and significantly decrease serum PCSK9 level in C57BL/6 mice. Application of this generalizable strategy will facilitate broad nanoparticle development for a variety of disease targets amenable to protein delivery and precise gene correction approaches.